Un sogno e l'amore: nota su due piccoli dipinti giovanili di Raffaello - Canavero, Alessandra Tarabochia (Verbum – Analecta Neolatina, 2005)
Two allegorical paintings by Raphael - Knight's Dream or (Scipio's Dream) and the Three Graces - should be considered as bearers of a single message. The three classical life styles, i.e., intellectual, active and voluptuous, symbolized by a book, a sword, and a small branch of myrtle, which two young women show to the sleeping knight, are not incompatible, but reconcilable, as Marsilio Ficino writes to Lawrence the Magnificent. All this is seen by the knight in his dream. The dream, as vacatio animae, is the site of possibility and conciliation. The three Graces show this in the reality, with their ideal dance, expression of the harmony of the opposites, fulfilled by love.